2009
DOI: 10.1093/hmg/ddp011
|View full text |Cite
|
Sign up to set email alerts
|

Copy number variants, diseases and gene expression

Abstract: Copy number variation (CNV) has recently gained considerable interest as a source of genetic variation likely to play a role in phenotypic diversity and evolution. Much effort has been put into the identification and mapping of regions that vary in copy number among seemingly normal individuals in humans and a number of model organisms, using bioinformatics or hybridization-based methods. These have allowed uncovering associations between copy number changes and complex diseases in whole-genome association stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
283
1
10

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 390 publications
(308 citation statements)
references
References 83 publications
9
283
1
10
Order By: Relevance
“…However, this assumption cannot be used to explain the negative correlations between gene copy number and expression level. Schlattl et al (2011) found that $20% of associations of CNVs displayed the unexpected negative correlations, including several instances that had been previously observed (Stranger et al 2007a;Henrichsen et al 2009). …”
Section: Roles Of Cnv and Natural Selectionsupporting
confidence: 55%
“…However, this assumption cannot be used to explain the negative correlations between gene copy number and expression level. Schlattl et al (2011) found that $20% of associations of CNVs displayed the unexpected negative correlations, including several instances that had been previously observed (Stranger et al 2007a;Henrichsen et al 2009). …”
Section: Roles Of Cnv and Natural Selectionsupporting
confidence: 55%
“…Deletions, in the presence of other schizophrenia genetic risk factors, may be directly interrupting one or more of these systems resulting in reduced neural efficiency and dysfunctional connectivity, leading to greater cognitive dysfunction. However, CNVs may also be affecting the expression and regulation of genes other than those directly affected by the CNV itself [91]. Further In sum, the current study replicated previous findings concerning the relationship between rare deletions and general cognition and extended the findings, identifying grey-matter volume differences in the striatum and right superior temporal gyrus and functional connectivity differences in cognitive control and default mode resting state networks.…”
Section: Iq -Neuroimaging Correlationssupporting
confidence: 88%
“…Identification of deletions and translocations in POF1 and POF2 regions has suggested several POF-candidate genes, such as [36][37][38], although very few mutations have actually been detected in these loci [39,40].…”
Section: Candidate Genes On the X Chromosomementioning
confidence: 99%
“…The CNV, defined as regions of DNA larger than 1 kb that display copy number differences in the normal population, contribute to genetic variation associated with diseases or susceptibility to diseases [40]. Indeed, CNV can influence transcriptional and translational levels of overlapping or nearby genes [91].…”
Section: Cnv In Pofmentioning
confidence: 99%